2012
DOI: 10.1161/atvbaha.111.242685
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2 Proteolysis of Calponin-1 Contributes to Vascular Hypocontractility in Endotoxemic Rats

Abstract: Objective-Matrix metalloproteinase (MMP)-2 is activated in aorta during endotoxemia and plays a role in the hypocontractility to vasoconstrictors. Calponin-1 is a regulator of vascular smooth muscle tone with similarities to troponin, a cardiac myocyte protein that is cleaved by MMP-2 in myocardial oxidative stress injuries. We hypothesized that calponin-1 may be proteolyzed by MMP-2 in endotoxemia-induced vascular hypocontractility. Methods and Results-Rats were given a nonlethal dose of bacterial lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 47 publications
0
36
0
2
Order By: Relevance
“…In particular, these data suggest that the programming of ET-1 function by prenatal hypoxia resides upstream of ET-1 interaction with its receptors, possibly via increased bET-1 conversion to active ET-1, but once ET-1 is released from the endothelium, the course of events that follows is similar irrespective of prenatal treatment. Accumulating evidence indicates that other bET-1-converting enzymes, including MMP-2, neutral endopeptidase, and chymase, are upregulated in models of vascular pathophysiology, 23,26 which may contribute to enhanced ET-1 signaling. In the present study, we used a number of enzyme inhibitors and found that bET-1 conversion was largely attributable to ECE, based on the observations that the ECE inhibitor CGS35066 abrogated the majority of the contractile response to bET-1.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these data suggest that the programming of ET-1 function by prenatal hypoxia resides upstream of ET-1 interaction with its receptors, possibly via increased bET-1 conversion to active ET-1, but once ET-1 is released from the endothelium, the course of events that follows is similar irrespective of prenatal treatment. Accumulating evidence indicates that other bET-1-converting enzymes, including MMP-2, neutral endopeptidase, and chymase, are upregulated in models of vascular pathophysiology, 23,26 which may contribute to enhanced ET-1 signaling. In the present study, we used a number of enzyme inhibitors and found that bET-1 conversion was largely attributable to ECE, based on the observations that the ECE inhibitor CGS35066 abrogated the majority of the contractile response to bET-1.…”
Section: Discussionmentioning
confidence: 99%
“…All of these markers have highly correlation with all the physiological functions and pathological changes during vascular diseases. For example, loss of SM α-actin leads to VSMCs hyperplasia in vivo and in vitro [8]; calponin-1 is an actin-binding protein which is similar with SM22α and its degradation would result in decreased vascular contractile response [9]; MHCs expression is decreased in human coronary arteries after the fifth decade [10] and smoothelin-B deficiency can reduce vascular contractility and cardiac hypertrophy in mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-2 in particular has been extensively associated with pathological vascular remodeling [5]. Active MMP-2 cleaves calponin-1 in VSMC to change the phenotype to a dedifferentiated state with reduced vasoconstriction ability, increases phosphorylation of extracellular signal regulated kinase 1/2 (ERK1/2) to increase VSMC proliferation, and cleaves membrane basement proteins to induce migration [22,23]. VSMC displayed increased levels of MMP-2 under mechanical stretch and this effect was blunted when cells were treated with OPN siRNA and in OPN deficient cells (gene level) and when using an OPN neutralizing antibody (protein level) [8].…”
mentioning
confidence: 99%